Faktor-Faktor yang Berhubungan dengan Risiko Kecacingan pada Anak Sekolah Dasar di Kota Ternate - Liasari Armaijn; Dewi Darmayanti; Sonia Buyung; Rochmat Hidayat (Universitas Malahayati Lampung, 2023)
ABSTRACT Disability is one of the neglected tropical infectious diseases (NTD) and is still a health problem in the world. More than 1.5 billion people or 24% of the world's population are infected with earthworms. More than 270 million children of preschool age and more than 600 million children of school age live in areas, where parasitic worms spread intensively, requiring treatment and prevention. The prevalence of helminthiasis in Indonesia in general is still very high, especially in the underprivileged population, with poor sanitation. The prevalence of helminthiasis varies between 2.5%-62%. Worm species that infect humans include roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura) and hookworms (Necator americanus and Ancylostoma duodenale) or known as Soil Transmitted Helminth (STH). For the past 3 years, not all health centers in Ternate City have also provided deworming. In fact, the data shows a downward trend, namely in 2020, only 8 out of 11 health centers (72%) gave deworming to elementary school students. Meanwhile, in 2021 there were 7 puskesmas (63.6%) and in 2022 there were 5 puskesmas (45.5%). To find out the factors related to the risk of helminthiasis in elementary school children in Ternate City. This study is an observational descriptive study. The research sample of 171 respondents was obtained using cluster random sampling and simple random sampling methods. The most respondents were women as many as 97 respondents (56.7%), the most respondents in Kalumata were 40 respondents (23.4%), the most knowledge level was good knowledge as many as 81 respondents (47.4%) and good attitudes as many as 72 respondents (42.1%).Environmental sanitation, level of knowledge and attitude towards helminthiasis are risk factors for the incidence of disability in children in elementary schools in Ternate City Keywords: Disability, Elementary School Children, Ternate City ABSTRAK Kecacingan merupakan salah satu penyakit infeksi tropis terabaikan (Negleted Tropical Disease/NTD) serta masih menjadi masalah kesehatan di dunia. Lebih dari 1,5 miliar orang atau 24% dari populasi dunia terinfeksi cacing tanah. Lebih dari 270 juta anak usia prasekolah dan lebih dari 600 juta anak usia sekolah tinggal di daerah, dimana cacing parasit menyebar secara intensif, sehingga membutuhkan pengobatan dan pencegahan. Prevalensi kecacingan di Indonesia pada umumnya masih sangat tinggi, terutama pada golongan penduduk yang kurang mampu, dengan sanitasi yang buruk. Prevalensi kecacingan bervariasi antara 2,5%-62%. Spesies cacing yang menginfeksi manusia diantaranya cacing gelang ( Ascaris lumbricoides ), cacing cambuk ( Trichuris trichiura ) dan cacing tambang ( Necator americanus dan Ancylostoma duodenale ) atau yang dikenal sebagai Soil Transmitted Helminth (STH). Selama 3 tahun terakhir, belum semua puskesmas di Kota Ternate juga memberikan obat cacing. Bahkan data menunjukkan tren penurunan yakni tahun 2020 hanya 8 dari 11 puskesmas (72%) yang memberikan obat cacing pada siswa SD. Sedangkan tahun 2021 sebanyak 7 puskesmas (63,6%) dan tahun 2022 sebanyak 5 puskesmas (45,5%). Untuk mengetahui faktor-faktor yang berhubungan dengan risiko kecacingan pada anak sekolah dasar di Kota Ternate. Penelitian ini adalah penelitian deskriptif observasional. Sampel penelitian sebanyak 171 orang responden diperoleh dengan metode cluster random sampling dan simple random sampling. Responden terbanyak adalah perempuan sebanyak 97 responden (56,7%), alamat responden terbanyak di Kalumata sebanyak40 responden (23,4%), tingkat pengetahuan terbanyak adalah pengetahuan baik sebanyak 81 responden (47,4%) dan sikap baik sebanyak 72 responden (42,1%). Sanitasi lingkungan, tingkat pengetahuan dan sikap terhadap kecacingan menjadi faktor risiko kejadian kecacingan pada anak di Sekolah Dasar di Kota Ternate. Kata Kunci: Kecacingan, Anak Sekolah Dasar, Kota Ternate